Provisioning, self-efficacy, and women’s economic crime: a quantitative examination - Molinet, MariTere (Deviant behavior, 2023)
A growing body of qualitative, agency-oriented research depicts women involved in crime as rational agents who, like men, pursue economic crime for a variety of reasons. This body of work also highlights the gendered nature of economic crime. Consistent with the roles, resources, and opportunities available to women, qualitative researchers argue that women who offend are especially likely to pursue economic crime as a means of "provisioning;" that is, to provide for the material betterment of family members and others close to them. For women, such provisioning may contribute to a sense of self-worth and personal competence, including a high level of "criminal self-efficacy." In this study, we seek to supplement and extend this body of qualitative research by providing a quantitative examination and by conducting systematic gender comparisons. Based on survey data collected from a sample of incarcerated men and women, our findings are generally in line with agency-oriented qualitative research. In comparison to the men in our study, women are more likely to cite provisioning as a motivation for economic crime. Further, their levels of criminal self-efficacy exceed those reported by men. We discuss the implications of our findings for the understanding of offender motivation and crime control policy.